Generation and performance assessment of the global TanDEM-X digital elevation model - Rizzoli, Paola; Martone, Michele; Gonzalez, Carolina; Wecklich, Christopher; Tridon, Daniela Borla; Braeutigam, Benjamin; Bachmann, Markus; Schulze, Daniel; Fritz, Thomas; Huber, Martin; Wessel, Birgit; Krieger, Gerhard; et al. (Isprs Journal of Photogrammetry and Remote Sensing, 2017)
The primary objective of the TanDEM-X mission is the generation of a global, consistent, and high-resolution digital elevation model (DEM) with unprecedented global accuracy. The goal is achieved by exploiting the interferometric capabilities of the two twin SAR satellites TerraSAR-X and TanDEM-X, which fly in a close orbit formation, acting as an X-band single-pass interferometer. Between December 2010 and early 2015 all land surfaces have been acquired at least twice, difficult terrain up to seven or eight times. The acquisition strategy, data processing, and DEM calibration and mosaicking have been systematically monitored and optimized throughout the entire mission duration, in order to fulfill the specification. The processing of all data has finally been completed in September 2016 and this paper reports on the final performance of the TanDEM-X global DEM and presents the acquisition and processing strategy which allowed to obtain the final DEM quality. The results confirm the outstanding global accuracy of the delivered product, which can be now utilized for both scientific and commercial applications.
DLR Import::2019-04-02
Keywords: Bistatic SAR; Digital elevation model (DEM); Interferometry; Remote sensing; TanDEM-X